Experimental verification of formation of readiness for professional activity with the use of interactive technologies of future geography teachers - Adobovska, Mariia Volodymyrivna (Journal of Education, Health and Sport, 2018)
The article defines that today, the priority task of modern pedagogical science is the development of the theoretical and methodological foundations of innovative processes, the study of the interrelations of theory and practice. Therefore, there is a need to determine the organizational and pedagogical conditions and test their effectiveness on the way to improve the professional training of modern specialists in the field of study. The article considers the developed author’s structural-functional model of formation of readiness of future teachers of geography to professional activity, which acts as a system of interrelated elements: goals, objectives, methodological approaches and principles, structural and functional components, content, forms, methods, results, as well as criteria and indicators of the level of formation of readiness for professional activity. The article presents the results of an experimental verification of the effectiveness of introducing a structural-functional model of the formation of readiness of future teachers of geography to professional activity using interactive technologies and testing the success of its functioning in the created organizational and pedagogical conditions. In the course of the experiment, on the basis of certain levels of structural components of readiness, data were obtained on the formation of readiness for professional activity in the experimental and control groups. The results obtained will allow us to conclude that the model we have proposed is effective and appropriate for its introduction into the process of professional training of future teachers of geography.